A novel 2D zinc(II)-organic framework for efficient catalytic cycloaddition of CO2 with epoxides. (1st July 2022) - Li, He-Juan; Zhang, Xiang-Yu; Huang, Kun; Qin, Da-Bin
Graphical abstract: The novel MOF Zn(dibpca)(OAc) was designed and synthesized based on a new imidazole carboxylic acid ligand, H-dibpca. The MOF exhibited superior activity for the catalytic cycloaddition of CO2 with epoxides under mild conditions. Abstract: The catalytic cycloaddition of CO2 with epoxides is an essential approach for CO2 fixation, but noble metal free heterogeneous systems with milder conditions are still required. Hence, a novel zinc-organic framework based on imidazole carboxylic acid with a two-dimensional (2D) layer structure was designed and synthesized for this reaction. The MOF was determined to be {[Zn(dibpca)(OAc)]·2.5H2 O}n (H-dibpca = 3′, 5′-di(1H-imidazol-1-yl)-[1, 1′-biphenyl]-4-carboxylic acid) by SC-XRD analysis, simplified as Zn(dibpca)(OAc), and further characterized by XPS, SEM, EDS, PXRD, FT-IR, TG and N2 -sorption analysis. The developed Zn(dibpca)(OAc), along with n -Bu4 NBr (TBAB) as a co-catalyst, exhibited efficient activity and high selectivity for the catalytic cycloaddition of CO2 with epoxides. The conditions are very mild: no catalyst activation, atmospheric CO2 pressure, low catalyst loading and no solvent. Multiple exposed Lewis acid sites on Zn(dibpca)(OAc), caused by the long rigid ligand and low coordination numbers, may contribute to the efficient catalytic performance. Various epoxides with different electronic and steric effects were evaluated and a slight influence was shown for both the yield and selectivity. In addition, the heterogeneous catalyst also showed good performance after being reused at least five times.